Bod's new leaf: making a fresh start - Cole, Alison; Cole, Lo (Contender London, 2003)
**Bod's New Leaf: Making a Fresh Start** is a heartwarming story that follows Bod, a young character who is ready to embrace change and growth in his life. As he navigates challenges and self-discovery, Bod learns the importance of resilience, friendship, and making positive choices. Throughout the story, Bod encounters obstacles but finds support from friends who encourage him to turn over a new leaf. The narrative emphasizes themes of hope and transformation, illustrating that it's never too late to start anew and pursue one's dreams. With relatable characters and an uplifting message, this book inspires readers to embrace their own journeys of self-improvement and renewal.